2018
DOI: 10.1039/c7en01120b
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of nano-scale and micro-scale zero-valent iron particles on planktonic microorganisms from natural reservoir water

Abstract: This study compares the effect of nanoscale and microscale zerovalent iron on natural freshwater microplankton over 21 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…These observational findings that nZVIs significantly reduce the toxicity and environmental impact of PCP are potentially very significant and additional studies were completed to more fully understand the mechanisms of action. 17 Interestingly, chlorophenols (CPs) analysis showed that without nematodes the degradation abilities of different ZVIs for PCP were comparable (Figure 1d), with the residual parent PCP concentrations ranging from 0.117 to 0.142 mmol/kg (31.1−37.9 mg/kg). This weakened nanoscale size effect of nZVIs has previously been reported in soil remediation studies and may be due to the homo-and heteroaggregation of nZVIs, with subsequent overall loss in reactivity.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These observational findings that nZVIs significantly reduce the toxicity and environmental impact of PCP are potentially very significant and additional studies were completed to more fully understand the mechanisms of action. 17 Interestingly, chlorophenols (CPs) analysis showed that without nematodes the degradation abilities of different ZVIs for PCP were comparable (Figure 1d), with the residual parent PCP concentrations ranging from 0.117 to 0.142 mmol/kg (31.1−37.9 mg/kg). This weakened nanoscale size effect of nZVIs has previously been reported in soil remediation studies and may be due to the homo-and heteroaggregation of nZVIs, with subsequent overall loss in reactivity.…”
Section: Resultsmentioning
confidence: 96%
“…Both before and after the 3 days of exposure, soil pH remained constant, but by the end of the exposure period, the increase in redox potention ( E h ) induced by PCP contamination was largely neutralized by nZVI 20 addition (Table S2). These observational findings that nZVIs significantly reduce the toxicity and environmental impact of PCP are potentially very significant and additional studies were completed to more fully understand the mechanisms of action …”
Section: Results and Discussionmentioning
confidence: 99%
“…But frequently such conditions are short-lived (El-Temsah et al 2013), and oxygen will diffuse in from the border zones and re-establish oxygenated conditions and alleviate the stress caused by the reduced O 2 availability. For those organisms that have survived the period of reduced O 2 availability, the effects may be fully reversible, with no negative impacts on populations or communities (Nguyen et al 2018a). Thus, if the exposure ceases and the organism has avoided it or only passed through a period with sub-optimal living conditions (stress) due to the nanoparticle exposure, it is not appropriate to interpret this as toxicity.…”
Section: Endpoint Selectionmentioning
confidence: 99%
“…From basic research in fields as disparate as evolutionary biology or the mechanisms of photosynthesis, to applied research on subjects from biofuel production to nuclear waste remediation, there is general interest in improving our basic understanding of bacteria and bacterial cultures. [1][2][3][4][5][6][7][8][9][10] In a variety of important situations, bacterial cultures in fluid media are optically thin or optically dilute systems such that light can be propagated into a culture and subsequently detected outside, all in the single scattering regime. This paper is about obtaining quantitative information from such mildly turbid systems, noninvasively and continuously.…”
Section: Introductionmentioning
confidence: 99%